Beet supplementation mitigates post-exercise inflammation - Nieman, David C.; Sakaguchi, Camila A.; Williams, James C.; Mulani, Fayaj A.; Shivprasad Suresh, Patil; Omar, Ashraf M.; Zhang, Qibin (Frontiers in Nutrition, 2024)
Objectives: This study investigated the efficacy of a mixed beet-based supplement (BEET) versus placebo (PL) in countering inflammation during recovery from 2.25 h of intensive cycling in 20 male and female cyclists. A multi-omics approach was used that included untargeted proteomics and a targeted oxylipin panel. Methods: A randomized, placebo-controlled, double-blind, crossover design was used with two 2-week supplementation periods and a 2-week washout period. Supplementation periods were followed by a 2.25h cycling bout at close to 70%VO2max. The BEET supplement provided 212 mg of nitrates per day, 200 mg caffeine from green tea extract, 44 mg vitamin C from Camu Camu berry, B-vitamins from quinoa sprouts (40% Daily Value for thiamin, riboflavin, niacin, and vitamin B6), and 2.5 g of a mushroom blend containing Cordyceps sinensis and Inonotus obliquus. Six blood samples were collected before and after supplementation (overnight fasted state), immediately post-exercise, and at 1.5h-, 3h-, and 24h-post-exercise. Results: The 2.25 h cycling bout increased plasma levels of 41 of 67 oxylipins detected. BEET supplementation significantly increased plasma nitrate (NO3-) and nitrite (NO2-) (sum, NO3- + NO2-) concentrations (interaction effect, p<0.001) and two anti-inflammatory oxylipins [18-hydroxyeicosapentaenoic acid (18-HEPE) and 4‐hydroxy‐docosahexanoic acid (4‐HDoHE)]. The untargeted proteomics analysis identified 616 proteins (458 across all times points), and 2-way ANOVA revealed a cluster of 45 proteins that were decreased and a cluster of 21 that were increased in the BEET versus PL trials. Functional enrichment supported significant BEET-related reductions in inflammation-related proteins including several proteins related to complement activation, the acute phase response, and immune cell adhesion, migration, and differentiation. Discussion: Intake of a BEET-based supplement during a 2-week period was linked to higher plasma levels of NO3- + NO2-, elevated post-exercise levels of two anti-inflammatory oxylipins, and a significant decrease in a cluster of proteins involved in complement activation and inflammation. These data support that 2-weeks intake of nitrate from a mixed beet-based supplement moderated protein biomarkers of exercise-induced inflammation in athletes.